Kontribusi Self-Efficacy terhadap Test Anxiety pada Mahasiswa Universitas ‘X’ Bandung - Tiffany Tan; Lisa Imelia Satyawan (Humanitas (Jurnal Psikologi), 2024)
Students tends to be test-anxious because they do not believe in their ability. This study aims to determine the effect of self-efficacy on students' test anxiety in X University Bandung. The respondents are 380 active undergraduate students at X University Bandung who were recruited through snowball sampling. The result of linear regression analysis concluded that self-efficacy has a negative and significant effect on students' test anxiety in 'X' University Bandung (B = -0.752, R2 = 0.339, p = -0.482). 33.90% of the students' test anxiety could be explained by their self-efficacy while 66.10% is influenced by other variables that are not examined in this study. Interventions are suggested to be given to the students to increase their self-efficacy thus they would no longer feel anxious during exams. Further research is suggested to use other sampling techniques and examine the determinants and sources of self-efficacy and test anxiety.